Integrating Sustainable Development into Indonesia’s Banking Architecture: Legal Perspectives on ESG-Driven Green Economy Policies in Sharia Banking (Architecture Image Studies, 2025)
The increase in human civilization usually brings forth negative impacts on the environment. With this rate of damage, various parties need to carry out efforts to prevent environmental destruction, such as through the initiation of green finance programs, which were enacted in Financial Service Authority Regulation (FSAR) No. 51 of 2017. This law contains the obligation of financial institutions, including sharia banks, to issue sustainable reports. These reports may be seen from three main factors, namely the environmental, social, and governance (ESG) sectors in the Bank Syariah Indonesia (BSI), to achieve the green banking concept. The implementation of the green banking concept allows the achievement of economic development goals with an environmental perspective. In this research, BSI is the analyzed object as it is the only sharia bank that is categorized as The highest Core-Capital-Based Public Bank and has complete and measurable sustainability reports. The objective of this research is to map out the effectiveness of this sharia bank’s ESG application as a manifestation of the green banking concept’s application. This article employed the descriptive qualitative method, which collected literary data. The results of this study indicate that although ESG reporting is mandatory for banks, its implementation has not been well-executed, as it appears to be a one-off report, and lacking uniformity. This serves as a reminder for policymakers to pay more attention to the content and substance of sustainability reports so that banks can effectively fulfill this obligation.